Comparison of Rotterdam and Helsinki Computed Tomography Scoring System in Predicting Outcome in Patients with Traumatic Brain Injury - Gurung, Ashim; Karki, Anjan Singh; Shrestha, Gyaneswhor; Shrestha, Dipendra Kumar; Pradhanang, Amit B; Sedain, Gopal; Shilpakar, Sushil Krishna; Sharma, Mohan Raj (Nepal Journal of Neuroscience, 2024)
Introduction: Traumatic brain injury (TBI) is a global public health problem. Different studies related to prognostic models have been performed previously to predict the outcome after TBI. The comparison between Rotterdam and Helsinki scores has been done in patient population in other countries. The main objective of this study is to compare these two scoring systems for prediction of outcome after TBI in Nepalese patient population.Materials and Methods: This is a prospective observational study done in the Department of Neurosurgery, Tribhuvan University Teaching Hospital from December 2019 to March 2021. Patients with TBI (mild complicated, moderate and severe) presenting to the hospital within 24 hours of injury were included. Their outcome was predicted on the basis of Rotterdam and Helsinki scores as per the Extended Glasgow Outcome Scale (GOSE) at the time of discharge and in six months.Results: A total of 88 patients with a mean age of 34.4 + 15.33 years were included with a male: female ratio of 6.3:1. The most common mode of injury was fall from height [43(48.9%)] followed by road traffic accidents [29(33%)] and physical assaults [14(15.9%)]. The majority of patients had a mild complicated head injury [56(63.6%)].81.8% patients had a favorable outcome in six months. The Rotterdam score had an AUC of (0.781 and 0.753) for mortality and unfavorable outcome. Similarly the Helsinki score had an AUC of (0.775 and 0.748) for mortality and unfavorable outcome respectively.Conclusion: Both scoring systems have high prediction for both unfavourable outcomes and mortality after TBI. However for prediction of outcome Rotterdam score was slightly superior to Helsinki Score but for mortality prediction Helsinki score was slightly better than the Rotterdam Score.